Cavas históricas de ouro do Jaraguá: o que resta para se preservar? - Carneiro, Celso Dal Ré; Santos, Luiz Fernando Dos; Silva, José Reynaldo Bastos Da [UNESP] (Sociedade Brasileira de Geologia, 2011)
The Historical “Jaraguá Gold Caves” are vestiges of excavations in weathered rock, dating back to the Brazilian colonial times, situated NW of Jaraguá peak, in the São Paulo municipality (SP). The areas were investigated to support historical preservation innitiatives. The excavations have lateral steep slopes and a narrow ﬂat bottom zone, occupied by dense vegetation. The trace of the excavations is sinuous, trending N40-50W, in accordance to a transition zone of Neoproterozoic rocks: metapelites and metapsamites by the SW side and calc-silicate rocks and amphybolites at NE. The structural control results from three successive deformation phases. Urban expansion and road construction, during the last 30 years, have strongly impacted the areas: (I) Base of Quebra-Pé hill; (II) Jardim Britânia; (III) Morro Doce; (IV) Nova Anhangüera Park. A 5th site was disfgured by earthworks. The Jardim Britânia area is partly discharacterized by earthflls; this however does not impede further protection actions. This framework allows to recommend authorities: (1) to permit immediate preservation of these areas; (2) to develop programs to build an integrated site for scientifc diffusion or an educational center for exhibition of rocks, ores and mineral samples; (3) to support the interest of some owners to preserve the area called “Morro Doce”, (4) to put forward a few proposals for educational use of the excavations, by production of feld guides on the historic sites. The alternatives will help keeping alive the memory of mining in the São Paulo State.

As áreas de ocorrência das “Cavas de Ouro Históricas do Jaraguá”, nos bairros Morro Doce e Jardim Britânia, município de São Paulo (SP), foram levantadas para apoiar medidas de preservação. As escavações, da época colonial, são ocupadas por densa vegetação; os taludes abruptos laterais delimitam fundos planos e estreitos. O traço sinuoso dos restos, orientado segundo N40-50W, acompanha zona de transição entre pacotes de rochas neoproterozoicas: a SW ocorrem metapelitos e metapsamitos e, a NE, rochas cálciosilicáticas e anfbolitos. As cavas são controladas por estruturas formadas em três fases de deformação. A expansão urbana e as rodovias, nas últimas três décadas, avançaram vigorosamente sobre os vestígios, porém ainda restam quatro, denominados: (I) Faldas do Morro do Quebra-Pé; (II) Jardim Britânia; (III) Morro Doce e (IV) Parque Nova Anhangüera. Um quinto local foi desfgurado por terraplenagem. A Cava do Jardim Britânia, parcialmente descaracterizada, sofreu aterramento parcial para construção de escola pública, mas ainda se pode propor medidas de proteção. Uma vez que as cavas estão bem preservadas, pode-se recomendar às autoridades que: (1) avaliem a alternativa do tombamento imediato das áreas; (2) desenvolvam programas para implantar sítios de divulgação científca ou um centro educacional integrado com exposição de amostras de rochas, minérios e minerais da região; (3) apoiem o interesse de alguns proprietários de preservar a área denominada “Cava Morro Doce”; (4) estimulem iniciativas de uso educativo das cavas, mediante produção de roteiros de visita aos sítios históricos. As alternativas ajudarão a recuperar parte da história da mineração paulista.
The Historical “Jaraguá Gold Caves”: what remains to be preserved?
Keywords: Geology; São Roque Group; mining; gold; heritage conservation; Geologia; Grupo São Roque; mineração; ouro; patrimônio histórico